TEACHING SIMPLE PAST TENSE IN NARRATIVE TEXT USING ANIMATION MOVIE THROUGH ONLINE LEARNING - Pabayo, Febriyanti Sonya; Rosnija, Eni; Wajdi, Majid (Journal of English Education Program, 2022)
The paper discusses the effectiveness of teaching simple past tense in narrative text using animation movie to increase students"™ grammar achievement of simple past tense in narrative text at the Eight grade students of SMP 1 Ngabang. The purpose of this research was to investigate the effect of teaching simple past tense in narrative text using animation movie through online learning to the Eight grade students of SMP Negeri 1 Ngabang in Academic Year 2021/2022. The research method was pre- experimental research with one group pretest-posttest design. The sample was the Eighth grade students that consisted of 7 students. The data was collected using measurement technique. The result of this research is analyzed by t-test. The t-ratio 9.58 was higher than the t-critical that was 2.093 on table distribution with Î± =0.05. Therefore, the alternative hypothesis (Ha) which stated "Teaching simple past tense in narrative text using an animation movie through online learning affect the students"™ achievement on the Eight-grade students of SMP Negeri 1 Ngabang was accepted. It showed that teaching simple past tense in narrative text using an animation movie through online learning affects students"™ grammar achievement of simple past tense.